Manajemen Program Pendidikan Kecakapan Hidup dalam Meningkatkan Kemandirian Peserta Didik di PKBM Handayani Bojonegoro - Cahyani, Arini Dwi; Mintarsih Arbarini; Tri Suminar (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
Lack of management of PKBM institutions makes some people less enthusiastic in participating in the implementation of the program. PKBM as an institution, forum, and place for community learning needs services. Entrepreneurship encourages community enthusiasm in learning. The objectives developed are to study and describe the management of life skills education programs in student independence at PKBM Handayani Bojonegoro. This study uses a qualitative approach with a survey. Data collection techniques, using in-depth interviews, participatory observation and documentation. The subjects of the study were managers, tutors, and students. Using qualitative analysis techniques with data reduction steps, data display, data verification for drawing conclusions. The results of the study showed that the development of the PKBM program followed the following steps: identifying learning needs, determining learning priorities, involving community leaders in preparing program planning, considering local potential and local wisdom; and entrepreneurship-based empowerment programs at PKBM, preparing programs that produce superior products for program sustainability, managers working professionally to make PKBM independent in each program, and opening networks with business partners for marketing superior products.